2019
DOI: 10.1007/s10393-019-01419-1
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat Factors Influenced the Prevalence of Pathogenic Leptospira spp. in Small Mammal Host

Abstract: Leptospirosis, a widespread zoonotic disease, is a public health problem, especially in major urban centres, and is mainly reported to be associated with rats. In Malaysia, focus has been primarily given to the Leptospira prevalence in rodents per se, but there is lack of information on the microhabitat structure of the outbreak areas. We aimed to determine the diversity of small mammal species, microhabitat types, and their prevalence of pathogenic Leptospira spp. in the outbreak areas, which were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
5
11
0
1
Order By: Relevance
“…Our findings confirmed that, at the city-scale, the prevalence of Leptospira carriage is heterogeneous (Himsworth et al 2013a;Krojgaard et al 2009;Minter et al 2019) and influenced by the microhabitat, as also demonstrated in (Yusof et al 2019). Our findings highlight that some urban sites, particularly those presenting blue infrastructures (e.g.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings confirmed that, at the city-scale, the prevalence of Leptospira carriage is heterogeneous (Himsworth et al 2013a;Krojgaard et al 2009;Minter et al 2019) and influenced by the microhabitat, as also demonstrated in (Yusof et al 2019). Our findings highlight that some urban sites, particularly those presenting blue infrastructures (e.g.…”
Section: Discussionsupporting
confidence: 87%
“…Overall, the diversity of small mammals in the mangrove forests was relatively poor (Shannon index of <1.0), compared to lowland (Yusof et al 2019) andhighland (Shukor et al 2001) forests in the Malaysian region. From this study, the least diverse small mammals were recorded at KST, which corresponded to the higher level of anthropogenic pressure, as indicated in Mohd-Taib et al (2020).…”
Section: Discussionmentioning
confidence: 91%
“…Occupational groups such as banana plantation farmers, sugarcane workers, paddy farmers, veterinarians, animal shelter employees, hunters, wet market workers and abattoir workers are at high risk of infection due to their job description involves contact with water and soils [69,70]. They are typically prone to skin cuts, abrasions during the activities in the particular areas which are providing a suitable environment and are rich with a source of food favouring the presence of rodents [71]. The rodent might share similar places with people, easily moving around and excreting bacteria into the environment via urine [72].…”
Section: Epidemiology Of Leptospiramentioning
confidence: 99%